Strengthening of the educational projects of the official educational institutions of the municipality of santiago de Cali (2019)
This article shows the results of an action research process, within the framework of the agreement between La Secretaria de Educación Municipal and the Instituto de Pedagogía de la Universidad del Valle, developed with 24 official educational institutions in order to restructure and update their Institutional Educational Project(IEP). For this, two strategies were used simultaneously between the months of August and December 2017. Firstly, a teacher training was required on aspects of the IEP, school and institutional characterization, and redefinition of the pedagogical model. Secondly, support and follow-up to each institution. The results show the scope and limitations of the experience, priorities and recommendations on the need to broaden the perspective of the educational community, from global to local, in coherence with the historical moment of construction of a culture of peace in the country.